OCEANIC VERSES OF THE QUR’AN AND THEIR POINTERS TO TECHNOLOGICAL SOLUTIONS - Jandra, Mifedwil; Anshori, Anhar; Kholili, H. M.; Rahman, Arif (Center for Research and Development of Religious Literature and Heritage, 2019)
This study aims to explore the phenomenon of the ocean recited in the verses of the Quran such as, fire/energy in the ocean, two oceans that do not blend, deep darkness of the ocean, sea boundary, oceanic layers, and the abundantwealth of the sea for humanity. This article focuses first on the semantic aspects on oceanic verses as revealed and found in 42 verses in the Quran and then how these verses could be used as guidance for technological solutions. The study uses the methodof interpretation of bir rakyi or interpretation within reason using the scientific method. Modern semantic scientific methods, ontology, and the categorization of verses are used for further understanding and developing a framework for further study in developing a foundation for Islamic Marine Knowledge. The study findings indicate that the knowledge of layers in the seawater column, as mentioned in the Quran, could be a blessing for Muslims to be inspired and guided to find more discoveries and benefitsof this water layer phenomenon. These ancient manuscripts are relevant to the challenges of modern civilization, such as food and energy security and environmental control. There are clues in these oceanic verses about technological solutions to the existing and future humanitarian problems, which Muslims can use as a divine guidance.